ENGLISH LEARNING MOTIVATION AND SPEAKING ABILITY - Sebastianus Menggo (Universitas Pendidikan Ganesha, 2018)
The aim of communicative language teaching is enable learners to communicate in the target language. A learner is sued to perform the micro and macro components in each utterance produced. Consequently, students need to know the linguistics forms, meanings and functions of that target language. They need to know that many different forms can be used to perform a function and also that single form can often serve a variety of functions. Students must be able to choose from among these the most appropriate form, given the social context and manage the process of negotiating meaning with their interlocutors. However, knowing learner’s English learning motivation is an urgent variable to be considered in creating conducive atmosphere classroom which will raise the learners to do more toward speaking achievement. The aim of this study is to know and describe the English learning motivation affecting students’ speaking ability of 48 students of XI grade of science program at catholic senior of Saint Ignasius Loyola Labuan Bajo, West Flores, Indonesia. Correlation design with purposive procedure applied in this research. Data were collected through questionnaire, interview, and students’ speaking document. Result shows that motivation is significantly affecting students’ speaking ability.